PERUBAHAN SISTEM BELANJA PERJALANAN DINAS PEMERINTAH DARI LUMPSUM MENJADI AT COST Kajian Kualitatif pada Sekretariat Daerah Kota Pekalongan - Fadilah, Sri; Nusantara, Agung (Jurnal Ilmiah Telaah Manajemen, 2016)
Goverment Official Travel Expenditure System Amendment becomes At Cost Per diems - Qualitative Study on the Regional Secretariat of Pekalongan. The purpose of this study is to investigate the implementation of official travel by the system at cost instead of the lump sum system, then what is perceived by the implementers tour of duty with the system at cost, through the perception of the respondents as well as the qualitative aspects of performance linkage efficiency, effectiveness and accountability of the official travel expenditure system at this cost. Type of research is the analysis of qualitative data, namely secondary data in the form of a review of definitions and concepts as well as the substance of some of the literature and legislation. In addition, primary data obtained from interviews of selected respondents, and relevant expert opinion in order to get conclusions about changes in the system of government business travel spending per diem be at cost, as well as the achievements of the efficiency, effectiveness and accountability of business travel spending in local government , especially the City of Pekalongan. The results of this study showed that after the implementation of Permendagri No. 16 of 2013, the implementation of official travel in Pekalongan, if the system is at cost as it is applied to the appropriate regulations is at cost to the cost of transport and accommodation expenses. Basically the perpetrators of this business trip or feel the presence of a potential lost opportunity, that should be their right, they feel economically disadvantaged as compared official travel when the per diem system. These conditions, can be demotivating for the players to make a business trip. Then the Local Government Mayor responded by issuing Regulation No. 20 of 2013, as the basis for standardization of the new prices official travel with the price adjustment points diem and lodging costs, so as to minimize the excesses of the application of laws and regulations in the area of the Central Government and the Central Government expectations will achieve efficiency, effectiveness and accountability of official travel shopping with this system change can be achieved. Keywords: Government Official Travel Expenditure, Per diems Systems, System At Cost.